Aplicación de un sistema de manejo de residuos sólidos en la I.E Jesús Alberto Miranda - Sánchez Piña, Gaby Paola (2010)
Currently, the garbage problem is so severe that generates air pollution, water and soil. The project improve solid waste management in educational institutions, allows for a proper management of refuse and waste, promote environmental awareness in the student population, prevent environmental pollution and reduce long-term environmental impact. This thesis document is structured based on a holistic approach to the problem, for which strategic purposes and order includes the following steps: First, a preliminary study of staff for the collection and analysis of existing information on solid waste management, taking into consideration operational and administrative aspects. This was followed by fieldwork for the study of situational analysis on solid waste management which was conducted a survey of students at the school, then was conducted to characterize the generation of so lid waste, calculations per-capita production, analysis of density and body composition. Finally, the system of solid waste management in that school, which was perceived results. All these aspects allow this document to maintain a functional and mostly technical, with a holistic approach to current reality of so1id waste management at the school"Jesús Alberto Miranda Street with technical areas"